Strategi Komunikasi Kepolisian Daerah Sumatera Barat (Polda Sumbar) Dalam Menunjang Kualitas Pelayanan Terhadap Masyarakat - Putra, Charlie Doma; Darwis, Yuliandre (CV. ITTC INDONESIA, 2024)
This research aims to describe and analyze the West Sumatra Regional Police (Polda Sumbar) Communication Strategy in Supporting Service Activities and to find obstacles in service faced by the Polda Sumbar. This study used qualitative research methods. In the era of increasingly rapid development of digitalization, the communication strategy applied in services has become the main factor in the implementation of services, good service is guaranteed by appropriate communication and digital developments make it easier for people to assess the quality of a service just through communication so that a good opinion is formed. Regarding this matter, the Polda Sumbar must implement objective, trustworthy communication and be participatory. Implementing appropriate communication strategies supports service activities at the Polda Sumbar .